Chemistry Teachers’ Ability to Design Classroom Action Research in Hybrid Learning Program - Antuni Wiyarsi (LPMPP Universitas Negeri Yogyakarta, 2017)
This research examines chemistry teachers’ understanding on Classroom Action Research (CAR) and their ability to design CAR in hybrid learning-based self-development program. The research employed one group pretest posttest design. Fifteen high school chemistry teachers in Sleman were involved. The program was carried out through course work and training following In-On-In format (face to face, practice, and face to face meetings). It was supported by the use of Tinular website (http://dikkitinular.wix.com/titinular). The research findings show that the increase of chemistry teachers’ understanding on CAR can be categorized as ‘medium’. Their ability to design a CAR can be categorized as ‘good’. The appropriateness of the action and data collection instrument constitute the ability with the lowest score. Continuous implementation of the program, appropriate supervision and scaffolding from the tutor significantly enhance teachers’ self-development. KEMAMPUAN MERANCANG PENELITIAN TINDAKAN KELAS GURU KIMIA DALAM PROGRAM BERBASIS HYBRID LEARNINGAbstrak: Penelitian ini bertujuan untuk menganalisis pemahaman guru kimia tentang penelitian tindakan kelas (PTK) dan kemampuan mereka dalam merancang PTK dalam program pengembangan diri berbasis hybrid learning. Desain penelitian yang digunakan one group pretest posttest design. Subjek penelitian adalah 15 orang guru kimia SMA di Kabupaten Sleman. Program pengembangan diri berbasis hybrid learning dilaksanakan melalui kegiatan pendidikan dan pelatihan dengan pola In-On-In. Program diawali dengan tatap muka, praktik dan ditutup dengan tatap muka. Selama pelaksanaan program didukung penggunaan website Tinular (http://dikkitinular.wix.com/titinular). Hasil penelitian menunjukkan bahwa pemahaman seluruh guru kimia tentang PTK mengalami peningkatan dengan kategori peningkatan “sedang”. Guru kimia memiliki kemampuan dalam merancang PTK dengan kategori baik. Ketepatan rancangan tindakan dan ketepatan instrumen pengambilan data merupakan indikator kemampuan dengan pencapaian terendah. Implementasi program yang kontinyu serta bimbingan dan scaffolding yang tepat dari tutor memberikan dukungan yang kuat bagi guru untuk pengembangan diri.